2007
DOI: 10.1097/aco.0b013e3281c10a08
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetics

Abstract: Local anesthetics have similar chemical structure but differing pharmacokinetic properties and spectra of pharmacodynamic effects that influence selection of agents for use in various clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 39 publications
1
104
0
16
Order By: Relevance
“…They are used in a wide range of clinical situations to prevent or reduce acute pain, chronic pain and cancer pain (2). A retrospective analysis of patients undergoing cancer surgery suggests that using regional anesthesia may reduce cancer recurrence and improve survival rate (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…They are used in a wide range of clinical situations to prevent or reduce acute pain, chronic pain and cancer pain (2). A retrospective analysis of patients undergoing cancer surgery suggests that using regional anesthesia may reduce cancer recurrence and improve survival rate (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In a review study conducted in 1995, Brown et al 7 reported a rate of 1.2 complications per 10,000 epidural anesthesias, similar what was found by Auroy et al 8 in France. New local anesthetics of long duration were synthetized and launched in the market such as ropivacaine and levobupivacaine which would be safer alternatives 9 . In 1998, Weinberg et al 10 demonstrated that a lipid emulsion (LE) was efficient in the treatment of local anesthetic cardiotoxicity, increasing by 50% the mean lethal dose of bupivacaine, however these solutions had been used for parenteral nutrition since 1961!…”
Section: Introductionmentioning
confidence: 99%
“…To varying extents, local anesthetics administered at appropriate concentrations may block both sensory and motor function in the innervated area [34]. High doses of local anesthetics have the potential to induce myotoxicity and neurotoxicity [2]. Although myotoxicity has been observed in laboratory studies of local anesthetics [35][36][37], clinically relevant myotoxicity appears to be rare [38].…”
Section: Risks Of Myotoxicity and Neurotoxicity With Local Anestheticsmentioning
confidence: 99%
“…Levobupivacaine, the S enantiomer of bupivacaine, was developed based on the belief that the pure S enantiomer would have less potential for toxicity than the R enantiomer and racemic mixture of bupivacaine [2,11]. However, the clinical relevance of this potential difference is unclear, as the safety profiles of bupivacaine and levobupivacaine appear to be very similar with standard/typical clinical usage [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation